Intensifying Functional Task Practice to Meet Aerobic Training Guidelines in Stroke Survivors - Kelly, Liam P.; Devasahayam, Augustine J.; Chaves, Arthur R.; Wallack, Elizabeth M.; McCarthy, Jason; Basset, Fabien A.; Ploughman, Michelle (Frontiers in Physiology, 2017)
Objective: To determine whether stroke survivors could maintain workloads during functional task practice that can reach moderate levels of cardiometabolic stress (i.e., ≥40% oxygen uptake reserve (V˙O2R) for ≥20 min) without the use of ergometer-based exercise. Design: Cross-sectional study using convenience sampling. Setting: Research laboratory in a tertiary rehabilitation hospital. Participants: Chronic hemiparetic stroke survivors (>6-months) who could provide consent and walk with or without assistance. Intervention: A single bout of intermittent functional training (IFT). The IFT protocol lasted 30 min and involved performing impairment specific multi-joint task-oriented movements structured into circuits lasting 3 min and allowing 30–45 s recovery between circuits. The aim was to achieve an average heart rate (HR) 30-50 beats above resting without using traditional ergometer-based aerobic exercise. Outcome measures: Attainment of indicators for moderate intensity aerobic exercise. Oxygen uptake (V˙O2), carbon dioxide production (V˙CO2), and HR were recorded throughout the 30 min IFT protocol. Values were reported as percentage of V˙O2R, HR reserve (HRR) and HRR calculated from predicted maximum HR (HRRpred), which were determined from a prior maximal graded exercise test. Results: Ten (3-female) chronic (38 ± 33 months) stroke survivors (70% ischemic) with significant residual impairments (NIHSS: 3 ± 2) and a high prevalence of comorbid conditions (80% ≥ 1) participated. IFT significantly increased all measures of exercise intensity compared to resting levels: V˙O2 (Δ 820 ± 290 ml min−1, p < 0.001), HR (Δ 42 ± 14 bpm, p < 0.001), and energy expenditure (EE; Δ 4.0 ± 1.4 kcal min−1, p < 0.001). Also, mean values for percentage of V˙O2R (62 ± 19), HRR (55 ± 14), and HRRpred (52 ± 18) were significantly higher than the minimum threshold (40%) indicating achievement of moderate intensity aerobic exercise (p = 0.004, 0.016, and 0.043, respectively). Conclusion: Sufficient workloads to achieve moderate levels of cardiometabolic stress can be maintained in chronic stroke survivors using impairment-focused functional movements that are not dependent on ergometers or other specialized equipment.